Pareto-efficient Tax Deductions - Sebastian Koehne; Dominik Sachs (Center for Economic Studies and ifo Institute (CESifo), 2019)
We analyze Pareto-efficient tax deduction rules for work-related expenses (e.g. housekeeping services, child care or elderly care). Pareto efficiency dictates a tight rule for how the rate of deductibility should vary with income and expenditures. An immediate implication is a recipe for designing Pareto-improving tax reforms. We apply our theory to housekeeping services in the U.S.: Introducing deduction rules such that between 55% (low expenses) and 85% (high expenses) of housekeeping services can be marginally deducted from taxable income yields a Pareto improvement if combined with a slight increase in marginal tax rates. Nobody is made worse-off and tax revenue increases by 20 Dollars per capita.
Keywords: D82; H21; 330; optimal taxation; tax deduction; Pareto-improving tax reform